The health promoting conversations intervention for families with a critically ill relative: A pilot study. (February 2019) - Ågren, S.; Eriksson, A.; Fredrikson, M.; Hollman-Frisman, G.; Orwelius, L.
Abstract: Background: After intensive care unit treatment, patients often have prolonged impairments that affect their physical, cognitive and mental health. Family members can face overwhelming and emotionally challenging situations and their concerns and needs must be addressed. Objective: We investigated the outcomes of pilot randomised control trial, a nurse-led family intervention, Health Promoting Conversations, which focused on family functioning and wellbeing in families with a critically ill member. Study design: This randomised controlled pilot study used a pre-test, post-test design with intervention and control groups to investigate the outcomes of the nurse-led intervention in 17 families. Outcome measures: The Health Promoting Conversations intervention was evaluated using validated instruments that measure family functioning and family wellbeing: the General Functioning sub-scale from the McMaster Family Assessment Device; the Family Sense of Coherence, the Herth Hope Index, and the Medical Outcome Short-Form Health Survey. Descriptive and analytical statistical methods were used to analyse the data. Results: After 12 months, the intervention group reported better family functioning than the control group. The intervention group also had better social functioning and mental health after 12 months. Conclusion: This intervention may improve family wellbeing by improving family function, reducing stress, and promoting better mental health.